(untitled) (Journal of actual problems of jurisprudence, 2019)
In given article it is told about the contract – as to the form of regulation of labour relations, the sphere of application of the contract and its feature also is described This article describes the difference of the labor contract and contractor’s agreement in area of public relations. Between these two contracts was provided comparative analysis and were detected analogy and distinctions.